Legal Analysis of Child Custody Rights Based on District Court Decision (Study of Decision No. 108/Pdt.G/2023/PN.Son) - Luhukay, Marlino Novlyson; Hasriyanti Hasriyanti (Journal of Law Justice (JLJ), 2025)
This study aims to understand the regulations regarding child custody under civil law and to analyze child custody after divorce based on the decision of the Sorong District Court with number 108/Pdt.G/2023/Pn.Son. This study uses an empirical legal research method, which combines literature study with direct interviews. Primary legal sources include interviews with relevant parties and applicable laws and regulations, while secondary legal sources are obtained from relevant academic articles. Data collection was conducted through interviews, and data analysis was performed qualitatively to gain a deeper understanding of the legal issues under study. The novelty of this research lies in its focus on analyzing the decision of the Sorong District Court Number 108/Pdt.G/2023/Pn.Son, which provides an assessment of child custody rights after divorce in the broader context of civil law. The results of the study show that although the Civil Code does not explicitly regulate child custody after divorce, the substance of the law emphasizes that children are entitled to fair treatment from both parents, both mother and father. The implementation of custody in the Sorong District Court decision was rejected by the Panel of Judges, taking into account various relevant legal factors. Based on the analysis of the decision, it can be concluded that the Panel of Judges carefully considered all legal aspects and facts of the trial. Custody of the child was granted to the biological mother (Defendant) because there was insufficient evidence to prove negligence in parenting. This decision is in line with Article 45(1) of the Marriage Law and the jurisprudence of the Supreme Court, which prioritizes the best interests of the child in custody arrangements following divorce.